Tracing the Pathways from Research to Innovation: Evidence from Case Studies. (11th April 2018) - Barjolle, Dominique; Midmore, Peter; Schmid, Otto
Summary: The complex process through which agricultural research stimulates innovation and achieves policy goals has commonly been treated as a 'black box' in the scientific literature. Statistical correlations between measured expenditure and impacts, where satisfactorily established, have mostly led to details of the research and innovation system being ignored. However, identifying and exploring causal chains of impact propagation can strengthen agricultural innovation. IMPRESA investigated impact mechanisms for research‐based innovations in six case studies using a Participatory Impact Pathway Assessment approach. Several suggestions result for improving performance and public support for agricultural research. Planning for impact is needed at the design phase of research so that expected advances in technology and their consequences can be explored. At that stage and throughout the research process, soft social skills are required to promote uptake. Greater impact can be achieved through the close involvement of key public and private sector stakeholders, using stakeholder mapping as a supporting tool. There is a strong argument for the close involvement of relevant social scientists and professional facilitators from the design phase of research through to its ultimate impacts. Funding frameworks and the specification of calls for tenders would function more effectively by giving more flexibility for stakeholder engagement. Abstract : The complex process through which agricultural research stimulates innovation and achieves policy goals has commonly been treated as a 'black box' in the scientific literature. Statistical correlations between measured expenditure and impacts, where satisfactorily established, have mostly led to details of the research and innovation system being ignored. However, identifying and exploring causal chains of impact propagation can strengthen agricultural innovation. IMPRESA investigated impact mechanisms for research‐based innovations in six case studies using a Participatory Impact Pathway Assessment approach. Several suggestions result for improving performance and public support for agricultural research. Planning for impact is needed at the design phase of research so that expected advances in technology and their consequences can be explored. At that stage and throughout the research process, soft social skills are required to promote uptake. Greater impact can be achieved through the close involvement of key public and private sector stakeholders, using stakeholder mapping as a supporting tool.